2007
DOI: 10.1126/science.1146663
|View full text |Cite
|
Sign up to set email alerts
|

Amazon Forests Green-Up During 2005 Drought

Abstract: Coupled climate-carbon cycle models suggest that Amazon forests are vulnerable to both long- and short-term droughts, but satellite observations showed a large-scale photosynthetic green-up in intact evergreen forests of the Amazon in response to a short, intense drought in 2005. These findings suggest that Amazon forests, although threatened by human-caused deforestation and fire and possibly by more severe long-term droughts, may be more resilient to climate changes than ecosystem models assume.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

28
481
5
12

Year Published

2010
2010
2015
2015

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 533 publications
(526 citation statements)
references
References 5 publications
28
481
5
12
Order By: Relevance
“…However, the magnitude and location of the sink of CO2 show large uncertainties [5,6], which lead to continuous researches focusing on monitoring vegetation activity change in the middle and high latitudes of the Northern Hemisphere. There are many investigations about the interannual variation in vegetation activity over the middle and high latitudes of the Northern Hemisphere based on the satellite-derived long-term records of Normalized Difference Vegetation Index (NDVI) data sets [7][8][9][10][11]. The vegetation activity in the northern middle and high latitudes demonstrated a consistent increasing trend according to the studies with the Global Inventory Monitoring and Modeling Studies (GIMMS) group produced NDVI data sets during 1981-1991 [12] and 1981-1999 [7].…”
Section: Introductionmentioning
confidence: 99%
“…However, the magnitude and location of the sink of CO2 show large uncertainties [5,6], which lead to continuous researches focusing on monitoring vegetation activity change in the middle and high latitudes of the Northern Hemisphere. There are many investigations about the interannual variation in vegetation activity over the middle and high latitudes of the Northern Hemisphere based on the satellite-derived long-term records of Normalized Difference Vegetation Index (NDVI) data sets [7][8][9][10][11]. The vegetation activity in the northern middle and high latitudes demonstrated a consistent increasing trend according to the studies with the Global Inventory Monitoring and Modeling Studies (GIMMS) group produced NDVI data sets during 1981-1991 [12] and 1981-1999 [7].…”
Section: Introductionmentioning
confidence: 99%
“…Data from conventional optical sensors suggested inconclusive results. One study showed the greening of the forest (increase in vegetation index) due to higher active radiation (less clouds) during the early stages of drought [14], while others proposed either browning of the forest from water stress [15], or greening in later stages of drought from opening of the canopy from potential tree mortality [16]. Satellite optical observations over tropical forests are impacted by clouds and atmospheric aerosol, causing noise in surface reflectance data [15].…”
Section: Introductionmentioning
confidence: 99%
“…Although severe soil moisture depletion during prolonged drought may lead to stomatal closure and a decline in leaf area (Nepstad et al, 1994), there is still controversy on whether draught-induced water deficit limits tree growth in the Central Amazon. During the 2005 drought, for example, Saleska et al (2007) reported an enhanced vegetation index of the forest based on moderate resolution imaging spectroradiometer (MODIS) satellite data. This is contrary to what should be expected, as changes in precipitation can alter growth rates (Lewis et al, 2004).…”
Section: Introductionmentioning
confidence: 99%